2006
DOI: 10.1038/sj.bjp.0706889
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic regulation of epithelial ion transport in the mammalian intestine

Abstract: Acetylcholine (ACh) is critical in controlling epithelial ion transport and hence water movements for gut hydration. Here we review the mechanism of cholinergic control of epithelial ion transport across the mammalian intestine. The cholinergic nervous system affects basal ion flux and can evoke increased active ion transport events. Most studies rely on measuring increases in short-circuit current (I SC ¼ active ion transport) evoked by adding ACh or cholinomimetics to intestinal tissue mounted in Ussing cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 202 publications
(226 reference statements)
6
112
0
Order By: Relevance
“…Indeed, the jejunum of HP piglets did not respond to carbachol (cholinergic agonist) or VIP as opposed to MF and AP piglets while in the ileum they did respond to VIP when MF and AP piglets did not. Such reduced response of the gut to cholinergic stimulation has been observed in various cases of gut dysfunction: electrolyte secretion in response to cholinomimetics was reduced in mice with T cell-driven enteropathies or rats infected with nematodes as a model of colitis (31); the smooth muscle contractile response to cholinergic stimulation was also reduced in the inflamed intestine (32). In the former study, altered acetylcholine metabolism 8 (increase AChE expression and activity, decreased packaging and exocytosis of acetylcholine, alteration of ChAT expression…) was involved (31).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the jejunum of HP piglets did not respond to carbachol (cholinergic agonist) or VIP as opposed to MF and AP piglets while in the ileum they did respond to VIP when MF and AP piglets did not. Such reduced response of the gut to cholinergic stimulation has been observed in various cases of gut dysfunction: electrolyte secretion in response to cholinomimetics was reduced in mice with T cell-driven enteropathies or rats infected with nematodes as a model of colitis (31); the smooth muscle contractile response to cholinergic stimulation was also reduced in the inflamed intestine (32). In the former study, altered acetylcholine metabolism 8 (increase AChE expression and activity, decreased packaging and exocytosis of acetylcholine, alteration of ChAT expression…) was involved (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still not clear whether these effects of EGC are direct effects on enterocytes or indirect effects via activation or inactivation of enteric neurons. It has been speculated that a possible effect of EGC could be via stimulation of enteric neurons, since neuronal effectors such as acetylcholine, vasoactive intestinal peptide, and nitric oxide are known key regulators of IEB (26,38). However, there is upcoming evidence showing that EGC directly regulate IEB.…”
Section: Effects Of Enteric Glial Cells On Intestinal Epithelial Barrmentioning
confidence: 97%
“…It is well known that neuronal effector proteins are involved in the regulation of IEB. Acetylcholine, vasoactive intestinal peptide, and nitric oxide influence mucosal blood flow, lymphocyte migration, mucus secretion, and resorption of nutrients (26,39). Overall, it has been demonstrated that activation of enteric neurons results in a stabilization of IEB.…”
mentioning
confidence: 99%
“…However, previous investigation suggested that the voltage-gated K ϩ channels regulated membrane potential, which was, in turn, important for the Na ϩ -dependent absorption of glucose and amino acids in the small intestine (37). Although the physiological functions of most swimming-altered genes have never been investigated, a number of genes are possibly involved in water and electrolyte homeostasis, such as cholinergic receptor, kallikrein-kinin, neuropeptide Y, aquaporin, renin, vasopressin, and galanin receptor (2,12,23,25,35,50). These genes could partially explain changes in water and electrolyte metabolism during exercise training (3).…”
Section: Discussionmentioning
confidence: 99%